(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2020)
The objective of this study was to evaluate the correspondence between characteristics of the teaching of Behavioral-Analytic Therapy and the knowledge of Behavior Analysis about teaching-learning processes. A systematic literature review was performed. The studies were selected on Scielo and PePSIC databases, on Sobre Comportamento e Cognição and Comportamento em Foco collections and in the main journals of Behavior Analysis in which Brazilians publish. The recovery of the studies was made using descriptors like “teaching” and “learning” in combination with “analytic-behavioral therapy” and “analytic-behavioral therapist”. 36 studies were identified and analyzed, in which information about teaching-learning processes, in general, presents a high level of generality, imprecision and little clarity, presenting little correspondence with analytic-behavioral knowledge regarding the teaching-learning processes. Nevertheless, recent studies present clearer information, indicating a possible tendency for researchers increasingly the base of their work on behavior analytic knowledge when teaching analytic-behavioral therapists.